The impact of rule modifications on elite basketball teams` performance - Ibanez, S. J.; Garcia-Rubio, J.; Gómez, M.-A.; Gonzalez-Espinosa, S. (Journal of Human Kinetics, 2018)
Rule modifications in basketball are used to develop the sport, and FIBA changes the basketball regulations periodically and constantly in search of a more attractive game. The objectives of this study were as follows: i) to characterise and identify the technical-tactical performance indicators which discriminated the game style according to the effect of rule modifications; and ii) to analyse the persistence of these indicators according to rule modifications over time. Analyses were made of all the editions of the current competition system of the Copa Del Rey in Spanish basketball. One hundred and forty matches were analysed, starting from the 1995-96 to the 2014-15 season. Data were gathered from the official competition web page (www.acb.com) The variables analysed included rule modifications, the number of ball possessions, points scored, one, two and 3-point field goals made and attempted, total rebounds, defensive and offensive rebounds, assists, steals, turnovers, blocked shots, dunks and committed and received personal fouls, score differences, as well as one, two and 3-point field-goal percentages. Several analyses were carried out: descriptive analysis to characterise the sample; ANOVA to identify differences between periods; discriminant analysis to determine technical-tactical performance indicators which best discriminated between each competition term and rule change period; and finally autocorrelation function and cross-correlation were used to estimate the persistency of performance indicators over time. Results show that rule changes affect the way basketball is played. Nevertheless, players and coaches are the ones who determine functional behavior in basketball.